2019
DOI: 10.3389/fonc.2019.01324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Magnetic Resonance Spectroscopy as a Tool for Monitoring Therapeutic Response of Whole Brain Radiotherapy in a Mouse Model for Breast-to-Brain Metastasis

Abstract: Brain metastases are the most common intracranial tumor in adults and are associated with poor patient prognosis and median survival of only a few months. Treatment options for brain metastasis patients remain limited and largely depend on surgical resection, radio- and/or chemotherapy. The development and pre-clinical testing of novel therapeutic strategies require reliable experimental models and diagnostic tools that closely mimic technologies that are used in the clinic and reflect histopathological and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Given recent reports on immune modulatory effects of ionizing radiation (IR), we evaluated effects of radiotherapy on the BrM TME. IR was applied as fractionated whole brain radiotherapy with 2 Gy on five consecutive days (5 × 2 Gy) in 1 arc using the Small Animal Radiation Research Platform (SARRP) (Wong et al, 2008) as previously described (Chae et al, 2019). Treatment was commenced when animals developed established metastatic lesions based on magnetic resonance imaging (MRI) (Fig 4A and B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given recent reports on immune modulatory effects of ionizing radiation (IR), we evaluated effects of radiotherapy on the BrM TME. IR was applied as fractionated whole brain radiotherapy with 2 Gy on five consecutive days (5 × 2 Gy) in 1 arc using the Small Animal Radiation Research Platform (SARRP) (Wong et al, 2008) as previously described (Chae et al, 2019). Treatment was commenced when animals developed established metastatic lesions based on magnetic resonance imaging (MRI) (Fig 4A and B).…”
Section: Resultsmentioning
confidence: 99%
“…BrM progression was monitored by MRI measurements until the trial end point. MRI was performed using a 7 Tesla Small Animal MR Scanner (PharmaScan, Bruker) with a volume coil as transmitter and a head surface coil for signal reception as previously described (Chae et al, 2019). Mice were injected intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetic resonance spectroscopy (MRS) is another imaging method that can be used to detect metabolic changes in the hippocampus in a noninvasive manner [21]. MRS can be used to monitor brain tumor progression and is helpful for identifying radiation necrosis after radiation therapy [22,23]. In studies of radiation brain damage, MRS has been shown to detect early metabolic changes in normal irradiated brain tissue [24][25][26].…”
Section: Introductionmentioning
confidence: 99%